2016
DOI: 10.1002/bjs.10154
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre observational study of outcomes after drainage of acute perianal abscess

Abstract: Recurrent abscess is rare and fistula occurs in one-quarter of the patients. Packing is painful and costly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…29 A recent multicentre observational study of 141 patients from the UK found that packing was costly and dressing changes were associated with a twofold to threefold increase in pain scores. 30 Whichever approach is used, monitor the wound for worsening symptoms, persistent or spreading cellulitis, malaise or pyrexia, and inflammatory markers and discuss with the surgical team in the presence of any of these symptoms.…”
Section: Postoperative Managementmentioning
confidence: 99%
“…29 A recent multicentre observational study of 141 patients from the UK found that packing was costly and dressing changes were associated with a twofold to threefold increase in pain scores. 30 Whichever approach is used, monitor the wound for worsening symptoms, persistent or spreading cellulitis, malaise or pyrexia, and inflammatory markers and discuss with the surgical team in the presence of any of these symptoms.…”
Section: Postoperative Managementmentioning
confidence: 99%
“…Anorectal abscesses are common, with 18 000 patients affected each year in England. The condition is treated primarily by incision and drainage in the operating theatre by a general surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…These abnormal crypts are predisposed to infection and abscess formation, which may be cured, recur, or develop into fistula-in-ano. 1,2,4,6,7 Recurrences and/or development of fistula-in-ano (RF) rates after treatment of perianal abscess are reported in 0 to 85% of cases. This wide range may be due to therapeutic differences (i.e., conservative management vs. surgical intervention) or conventions in reporting and designating fistulas as recurrences or complications.…”
Section: Introductionmentioning
confidence: 99%
“…This wide range may be due to therapeutic differences (i.e., conservative management vs. surgical intervention) or conventions in reporting and designating fistulas as recurrences or complications. [1][2][3][4][6][7][8][9] Although conservative management is the most frequently used and first-opted approach, surgical intervention, which includes incision and drainage (ID), drainage change alone, or fistulotomy of first-time perianal abscess, may be needed if the conservative treatment cannot control the condition. In fact, the indication for surgical intervention remains obscure and controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation